STUDY OF HbA1c AS A BIOMARKER IN DYSLIPIDEMIA AND ATHEROGENICITY IN TYPE 2 DIABETES MELLITUS - Rajlaxmi, Tiwari; SS, Ghangale; CM, Iyer (International Journal of Clinical and Biomedical Research, 2015)
HbA1c is being used to assess the glycemic control for many years. This study was done to evaluate the importance of HbA1c in predicting dyslipidemia and atherogenecity in type 2 Diabetes. Methods: 200 type 2 diabetic patients were taken as subjects. Fasting and post meal blood sugar, Glycated haemoglobin (HbA1c), lipid profile, lipid ratios and atherogenic index of plasma(AIP) was analysed in these patients. The patients were divided into 2 groups depending on their HbA1c; Good Glycemic Control was defined as having HbA1c ≤ 7.0% and Poor Glycemic Control as HbA1c >7.0%. Results & Discussion: We found a significant increase in the levels of blood glucose, total serum cholesterol (TC), triglyceride, LDL cholesterol (LDL-C) and VLDL cholesterol (VLDL-C), TC/HDL-C, LDL-C/HDL-C, atherogenic index of plasma (AIP) and a significant decrease in the levels of HDL cholesterol (HDL-C) in patients with HbA1c >7% as compared to patients with HbA1c ≤ 7%. HbA1c had a direct and significant correlation with TC, TG, VLDL-C, LDL-C, TC /HDL-C, LDL-C/HDL-C, and an inverse correlation with HDL-C. AIP correlates with cardiovascular risk very well, and the association between HbA1c with various lipid parameters and atherogenic ratios suggests the importance of glycemic control in order to control dyslipidemia and future risk of cardiovascular disease in type 2 diabetics. KEYWORDS: Lipid profile; Type 2 diabetes mellitus; Glycosylated haemoglobin; Glycemic control, Atherogenic index of plasma.